Alignment of Ge-imogolite nanotubes in isomalt with tunable inter-tube distances. Issue 34 (19th April 2017) - Levard, Clement; Thill, Antoine; Avellan, Astrid; Mauroy, Cyprien; Vidal, Vladimir; Campos, Andrea P. C.; Masion, Armand; Rose, Jerome
Abstract : This study shows the almost perfect alignment of inorganic nanotubes (Ge-imogolite) within polyol filaments. Abstract : This study shows the almost perfect alignment of inorganic nanotubes (Ge-imogolite) within polyol filaments. Alignment was obtained by simply cooling a Ge-imogolite–polyol mixture under mechanical stress. Additionally, inter-tube distances in the plane normal to the filaments can be tuned by simply varying the weight fraction of imogolite in the starting solution. The ease of the alignment protocol will stimulate interest for testing new applications which require a good control of the pore density and morphology (periodicity, and high monodispersity of the pore size distribution).